2016
DOI: 10.1088/0256-307x/33/6/066201
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Sandwich Ultra-Thin Silicon(100) Platform for Flexible Electronics

Abstract: As a potential flexible substrate for flexible electronics, a polymer-sandwiched ultra-thin silicon platform is studied. SU-8 photoresist coated on the silicon membrane improves its flexibility as shown by an ANSYS simulation. Using the plasma enhanced chemical vapor deposited SiO2/Si3N4 composite film as an etching mask, a 4″ silicon-(100) wafer is thinned to 26 μm without rupture in a 30 wt.% KOH solution. The thinned wafer is coated on both sides with 20 μm of SU-8 photoresist and is cut into strips. Then t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, the epoxy coated-CNF has proven to be more suitable for flexible microwave applications than for PET films [92]. Zhang, et al reported that the coating of photoresist SU-8 on a silicon-(100) wafer substantially improves the flexibility and can be used for high-performance flexible electronics [93], whereas developed glass/SU8-gold electrodes by Matarèse, et al were extremely transparent, and stable in the biological culture medium, which exhibited biocompatibility similar to glass [94]. Flexible and bendable (to 90 • ) tactile sensor arrays were also developed by Yeo, et al, consisting of aluminum nitride, based on micro-electro-mechanical system (MEMS) technology, where polydimethylsiloxane (PDMS) and a SU-8 photoresist layer were used as the supporting layers [95].…”
Section: High-k Dielectric Polymersmentioning
confidence: 99%
“…However, the epoxy coated-CNF has proven to be more suitable for flexible microwave applications than for PET films [92]. Zhang, et al reported that the coating of photoresist SU-8 on a silicon-(100) wafer substantially improves the flexibility and can be used for high-performance flexible electronics [93], whereas developed glass/SU8-gold electrodes by Matarèse, et al were extremely transparent, and stable in the biological culture medium, which exhibited biocompatibility similar to glass [94]. Flexible and bendable (to 90 • ) tactile sensor arrays were also developed by Yeo, et al, consisting of aluminum nitride, based on micro-electro-mechanical system (MEMS) technology, where polydimethylsiloxane (PDMS) and a SU-8 photoresist layer were used as the supporting layers [95].…”
Section: High-k Dielectric Polymersmentioning
confidence: 99%
“…Thinned silicon wafers with thicknesses of about 50 µm enable higher packaging densities for three-dimensional (3D) silicon integration and reduce the heat resistance to improve heat dissipation for increasingly powerful chips [1,2]. Moreover, thinning increases the mechanical flexibility of the wafers, which enables the utilization of thin silicon wafers for bendable and flexible devices [3,4]. However, the reduction of the wafer thickness causes new problems for established dicing methods.…”
Section: Introductionmentioning
confidence: 99%
“…These research studies dramatically speed up the flexibility transfer of current electronic devices. [5,6] Generally, the methods of flexibility transfer are divided into two categories: transfer-bonding and direct deposition. [7] For the transfer-bonding technique, the advantage is that theoretically this method is applied to all rigid inorganic devices if a suitable sacrifice layer is found.…”
mentioning
confidence: 99%